2003
DOI: 10.2337/diabetes.52.10.2594
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Induces Clonal Selection and Reversible Dinucleotide Repeat Expansion in Mesangial Cells Isolated from Glomerulosclerosis-Prone Mice

Abstract: Clonal selection has been proposed as a pathogenetic mechanism in various chronic diseases, such as scleroderma, hypertension, pulmonary fibrosis, interstitial fibrosis of the kidney, atherosclerosis, and uterine leiomyomatosis. We previously found that mesangial cells from ROP mice prone to develop glomerulosclerosis changed their phenotype in response to high glucose concentrations. Here, we investigate whether clonal selection might contribute to this phenotype change. We found that in ROP mice at least two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…43 Although not applicable to aging, per se, stable epigenetic changes in the matrix metalloproteinase-9 promoter could be induced by chronic hyperglycemia in vitro, a condition associated with increased formation of AGEs and increased OS. 48,49 We found that the reversibility of the phenotypic changes in the matrix metalloproteinase-9 promoter depended on the genetic background. 49 …”
Section: Studies In Micementioning
confidence: 87%
See 1 more Smart Citation
“…43 Although not applicable to aging, per se, stable epigenetic changes in the matrix metalloproteinase-9 promoter could be induced by chronic hyperglycemia in vitro, a condition associated with increased formation of AGEs and increased OS. 48,49 We found that the reversibility of the phenotypic changes in the matrix metalloproteinase-9 promoter depended on the genetic background. 49 …”
Section: Studies In Micementioning
confidence: 87%
“…Namely, the stable phenotypic changes in mesangial cells in vitro reflect the in vivo sclerotic glomerular changes. 47,48 The stable aging phenotype is proinflammatory and prosclerotic, as shown by gene expression analysis that revealed that the stable phenotypic changes in glomerular cells were proinflammatory and prosclerotic. 43 Although not applicable to aging, per se, stable epigenetic changes in the matrix metalloproteinase-9 promoter could be induced by chronic hyperglycemia in vitro, a condition associated with increased formation of AGEs and increased OS.…”
Section: Studies In Micementioning
confidence: 99%
“…For example, in a recent study, Fornoni et al observed that exposure of mesangial cells to high glucose concentrations in vitro induced MSI. Thus, dietary sugars, such as refined glucose, may create conditions to produce significant structural and biological alterations that might include genomic instability within DNA (31).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of Os/ϩ ROP mice show that they possess approximately 50% fewer nephrons in the Os/ϩ mice than in the ϩ/ϩ mice (160). In general, wild-type mice (Os ϩ/ϩ , Ra ϩ/ϩ , and Pt ϩ/ϩ ) of ROP background seem to be more prone to glomerulosclerosis than C57BL/6 mice after a reduction in renal mass (161)(162)(163). Mice on the ROP background, in the absence of Os, Ra, or Pt mutant alleles, may also exhibit increased propensity for glomerulosclerosis after combined nephron mass reduction and diabetes (146).…”
Section: Ropmentioning
confidence: 99%